Biopsychosocial aspects of older adults (males and females) participating in an extension project for health promotion (Research, Society and Development, 2021)
Introduction: While the population has lived longer, chronic non-communicable diseases (NCD’s) has also impacted a larger portion of the elderly population. Objective: To analyze possible correlations between the biopsychosocial variables of elderly, males and females, and compare the responses among them. Methods: This is a cross-sectional study, conducted in February/2020, in an extension project in Maringá/PR, with 30 older adults. Biochemical variables were analyzed (aspartate-AST and alanine aminotransferase-ALT, triglycerides-TG, total cholesterol-TC, high-density lipoproteins-HDL-c, low-density-LDL-c, very low-density-VLDL-c, alkaline  phosphatase-AP gamma-glutamyltransferase-GGT and fasting glucose-FBGL); Anthropometry/body composition (body mass index-BMI, skeletal muscle mass-SMM, fat mass-FM, and body fat-%BF); physical fitness (forearm flexion, flexibility, and 6-min walk test) and questionnaires (Body Shape Questionnaire-BSQ, Self-esteem, Anxiety-HAM-A and Sleep Quality of Pittsburg- PSQI). The correlations were interpreted according to Hopkins et al. (2009). Results: The general group presented correlations between %BF and TG (r=0.36-moderate effect); PSQI and HAM-A (r=0.44-moderate effect) and PSQI and FM (r=0.39-moderate effect) and for the female group, it were observed correlations between %BF and FBGL (r=0.54-large effect); %BF and TG (r=0.64-large effect); %BF and GGT (r=0.59-large effect); %BF and VLDL-c (r=0.63-large effect) and PSQI and HAM-A (r=0.72-very large effect), all with p0.05). Conclusion: The results indicated differences among males and females’ elderly adults, suggesting the need for adjustments to programs to combat NCD´s.